Immune Effects of γδ T Cells in Colorectal Cancer: A Review - Ma, Rulan; Yuan, Dawei; Guo, Yizhan; Yan, Rong; Li, Kang (Frontiers in Immunology, 2020)
Gamma delta (γδ) T cells can effectively recognize and kill colorectal cancer (CRC) cells, thereby suppressing tumor progression via multiple mechanisms. They also have abilities to exert protumor effect via secreting interleukin-17 (IL-17). γδ T cells have been selected as potential immunocytes for antitumor treatment because of their significant cytotoxic activity. Immunotherapy is another potential anti-CRC strategy after the operation, chemotherapy, and radiotherapy. γδ T cell-based immunotherapy for CRC shows fewer side effects and better toleration. This review will outline the immune functions and the mechanisms of γδ T cells in growth and progression of CRC in recent years, and summarize the immunotherapies based on γδ T cells, thus providing a direction for the future research of γδ T cells in CRC.